A rare anomaly of the right superior pulmonary vein: Report of a case. (2017) - Ichiki, Yoshinobu; Kakizoe, Kesei; Hamatsu, Takayuki; Suehiro, Taketoshi; Koike, Makiko; Tanaka, Fumihiro; Sugimachi, Keizo
Highlights: We experienced a an extremely rare anomaly of the right superior PV. Contrast-enhanced three-dimensional CT (3D-CT) showed that the right superior PV ran abnormally between the right main pulmonary artery (PA) and the right main bronchus. The anomaly reported in the present case has been reported in only one case report. Abstract: Introduction: Although there are a lot of variations of pulmonary veins (PVs) including dangerous type that could cause serous complications during the surgery, limited information has been reported about these variations. We have experienced an extremely rare anomaly of the right superior PV. Presentation of case: A 74-year-old man patient with right lung cancer visited our hospital. Chest computed tomography (CT) revealed a pulmonary nodule in the right lower lobe. Contrast-enhanced three-dimensional CT (3D-CT) showed that the right superior PV ran abnormally between the right main pulmonary artery (PA) and the right main bronchus. We performed right lower lobectomy and systematic nodal dissection. The operative findings confirmed that the right superior PV ran abnormally same as 3D-CT. Discussion: In most reported cases, anomalous PVs pass behind the right bronchi or into the roof of the left atrium. The anomaly reported in the present case has been reported in only one case report. This case suggests that the space between the right main PA and the right main bronchus is not always safe for dissection. Conclusion: Preoperative 3D-CT is useful for avoiding unexpected bleeding.